The Effect of the Electronic Subsystem on the Deformation and Stress Localization in the Surface Layer of Solids; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Khon Yu. A. Yury (2016, 2016)
Title screen